Vitamin D mitigates ethanol preference in rats via the DRD2-GDNF and antioxidant signaling in vivo: Vitamin D effect on ethanol CPP - Sadria, Sajjad; Alani , Behrang; Arjmand , Ali; Shahaboddin , Mohammad Esmaeil; Ahmadi Asouri , Sahar; Ghavipanjeh, Gholamreza; Ardjmand, Abolfazl (Iranian Journal of Pharmaceutical Sciences, 2025)
Alcohol abuse is a widespread mental disorder with significant health complications. A relationship between vitamin D (VitD) and ethanol abuse has been established. VitD, as a vital element for the development and metabolism of dopaminergic neurons, affects dopamine and glial cell line-derived neurotrophic factor (GDNF) synthesis and may play a role in the pathogenesis of alcohol-related disorders. In this study, we aimed to examine the role of VitD in the attenuation of ethanol-induced conditioned place preference in rats via dopamine D2 receptor-GDNF and antioxidant signaling in vivo. Rats were randomly divided into control, ethanol (Eth), and three Eth+VitD groups for behavioral experiments in conditioned place preference (CPP) and an open field. The activities of different brain oxidants (MDA, NO, and TOS), as well as antioxidative parameters (CAT, GPx, SOD, and TAC), plus oxidative stress index (OSI) and plasma VitD levels, were measured. Finally, hippocampal NOX, GDNF, and DRD2 expression were examined by western blotting. VitD (500 IU) combined with the effective dose of Eth (1.25 g/kg) resulted in the maximum decrease in CPP with no effect on locomotion. VitD supplementation elevated plasma VitD levels post-conditioning, increased the activities of brain antioxidants, and overexpressed hippocampal NOX, GDNF, and DRD2 proteins. We demonstrate that VitD attenuates alcohol-induced conditioning in rats via DRD2-GDNF and antioxidant signaling in vivo. Hence, targeting GDNF signaling may be a novel approach for the development of new drugs to treat Eth-related disorders among VitD users.